A modular ultra-high vacuum millikelvin scanning tunneling microscope - Wong, Dillon; Jeon, Sangjun; Nuckolls, Kevin P.; Oh, Myungchul; Kingsley, Simon C. J.; Yazdani, Ali (Review of scientific instruments, 2020)
We describe the design, construction, and performance of an ultra-high vacuum (UHV) scanning tunneling microscope (STM) capable of imaging at dilution-refrigerator temperatures and equipped with a vector magnet. The primary objective of our design is to achieve a high level of modularity by partitioning the STM system into a set of easily separable, interchangeable components. This naturally segregates the UHV needs of STM instrumentation from the typically non-UHV construction of a dilution refrigerator, facilitating the usage of non-UHV materials while maintaining a fully bakeable UHV chamber that houses the STM. The modular design also permits speedy removal of the microscope head from the rest of the system, allowing for repairs, modifications, and even replacement of the entire microscope head to be made at any time without warming the cryostat or compromising the vacuum. Without using cryogenic filters, we measured an electron temperature of 184 mK on a superconducting Al(100) single crystal.